APPLICATIONS IN CAR SALES SHOWROOM SPAREPART LATIEF USING MICROSOFT VISUAL BASIC AUTO 6.0 - Achmad Taufik; Aqwam Rosadi K., SKom, MM (Jurnal Sistem Informasi, 2007)
Scientific Writing describes the application of the Visual Basic language into thecalculation process and data items that still use Microsoft Excel on the system on theSale of Goods Latief Auto Showroom.This application program making process sales transactions of goods and sales reportsin order to more easily and efficiently. This application program can be stored so thatit can be used as an inventory control system to prevent future errors.In order to produce a better view, then this program is built using Microsoft VisualBasic 6.0. Also in this study also explained about the making of the applicationprogram.